2012
DOI: 10.1049/el.2012.0207
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of electromagnetic immunity of microcontrollers on system clock frequency

Abstract: To test and to model the conducted radio frequency electromagnetic immunity of a reconfigurable integrated circuit like microcontrollers is complex because the configuration parameter is variable. A study is presented of the dependence of immunity on one of the configuration parameters -the system clock. The theoretical analysis shows that the immunity is independent of the clock frequency in the frequency range of interest. Measurement results support the theoretical prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…However, as a basic configuration parameter in a microcontroller, the clock signal, which is variable in frequency, may cause great problems in the immunity test and modelling. A previous study [6] demonstrated that the immunity performance of microcontrollers is independent of the clock frequency when an RF noise is injected into the supply pins. However, in the case that RF noise is injected into a common I/O pin, the clock signal plays an important role when reading the input logic state from the data register, and this system clock effect is always ignored.…”
mentioning
confidence: 99%
“…However, as a basic configuration parameter in a microcontroller, the clock signal, which is variable in frequency, may cause great problems in the immunity test and modelling. A previous study [6] demonstrated that the immunity performance of microcontrollers is independent of the clock frequency when an RF noise is injected into the supply pins. However, in the case that RF noise is injected into a common I/O pin, the clock signal plays an important role when reading the input logic state from the data register, and this system clock effect is always ignored.…”
mentioning
confidence: 99%